Microscopy data set of mRNA FISH and Protein gene expression measurements in which repressor binding strength is systematically altered. - Kandavalli, Vinodh; Zikrin, Spartak; Elf, Johan; Jones, Daniel (Uppsala University, 2025)
This dataset contains the raw data, analysis and code needed to generate the figures presented in the paper "Anti-correlation of LacI association and dissociation rates observed in living cells" (see Related Material). The raw data consists of microscopy images and qPCR files. The analysis and code consist of data analysis, output from the analysis, its post-processing, simulations, and which figure the data was used in.

Experimental data, and analysis scripts are all organized using unique IDs (UID; seen for example in the filenames of experimental data below).

The README.txt file in the Analysis_of_data folder describes which UIDs for data, analysis, code & figure generation to combine for specific figures.

For the microscopy experiments (has the prefix Microscopy_Data_ in their filenames) there is information on the growth condition and which figure the data was used in. All experiments were performed at 30 degrees Celsius.

Details on the output from microscopy experiments can be found in the file MicroscopyInformation.txt.
Keywords: Systems biology; Gene expression (incl. microarray and other genome-wide approaches); Synthetic biology; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik; Biological Sciences; Biologi